Successful outcome of pregnancy in bicornuate uterus: a case report - Choudhary, Suman; Jelly, Prasuna; Mahala, Prakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Bicornuate uterus is a major cause of spontaneous abortion. The recurrent pregnancy loss has been reported to the range of 15% to 27%. There is different type of congenital uterine abnormalities like Bicornuate uterus, septate uterus, arcuate uterus, unicornuate uterus, didelphys uterus. It is important to consider this diagnosis in recurrent miscarriages, malpresentation, intra uterine growth restrictionand preterm deliveries. This report is about self at the age of 25-year-old pregnancy with a history of missed abortion. I was not diagnosing with a bicornuate uterus in my first pregnancy. However, I was diagnosed with a bicornuate uterus based on transvaginal ultrasound and hysterosalpingogram. A successful caesarean section was donein the 38th week of gestation. According to the results, successful outcome could be achieved with bicornuate uterus. The outcome of bicornuate uterus was successful.